2014
DOI: 10.1192/bjp.bp.113.134445
|View full text |Cite
|
Sign up to set email alerts
|

First-contact incidence of psychosis in north-eastern Italy: influence of age, gender, immigration and socioeconomic deprivation

Abstract: The incidence rate in our study area was lower than that found in other European and North American studies and provides new insights into the factors that may increase and/or decrease risk for developing psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 64 publications
12
43
0
Order By: Relevance
“…In previous studies, living in urban slum households with a poor quality of life was suggested to influence the mental health status of teenage girls [32,33]. Many studies supported that those living in poverty or lower socioeconomic status, disabled, housewives living in slums [44,45], and those living in the most deprived areas [46] are at risk of poor mental health status.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, living in urban slum households with a poor quality of life was suggested to influence the mental health status of teenage girls [32,33]. Many studies supported that those living in poverty or lower socioeconomic status, disabled, housewives living in slums [44,45], and those living in the most deprived areas [46] are at risk of poor mental health status.…”
Section: Discussionmentioning
confidence: 99%
“…[2628] Similarly, in a study examining the immigrant population in Italy, researchers found that immigrants have higher rates of all psychotic disorders compared with the general population. [29] Likewise, another international study found that immigrants were at a higher risk of schizophrenia when compared with native-born individuals. [30] Specifically, those who immigrate as youth are at higher risk[31, 30] than those who immigrate at older ages.…”
Section: Overview Of Risk and Protective Factorsmentioning
confidence: 99%
“…The study was designed to ensure comparable procedures and methods across settings, with some local adaptation to allow for variations in healthcare provision and health service contact points. The primary deviation from protocol was in the Veneto region, Italy, where data were derived from a previous study which used comparable methods [29], but had a lower upper-age limit of 54.…”
Section: Quality Assurance and Controlmentioning
confidence: 99%